Lilies of the field [videorecording (DVD)] - Nelson, Ralph, 1916-1987; Poitier, Sidney; Skala, Lilia; Adams, Stanley, 1915-1977; Barrett, William E. (William Edmund), 1900-1986 (MGM Home Entertainment, 2001)
A free-spirited ex-G.I. stumbles upon five German refugee nuns in Arizona and helps them build a chapel.